Mapeamento geoambiental dos municípios de Agudo, Dona Francisca, Faxinal do Soturno, Nova Palma Pinhal Grande - RS - Schirmer, Gerson Jonas (2012)
This paper presents a proposal for zoning in municipalities of geoenvironmental: Agudo, Dona Francisca, Faxinal the Soturno, Nova Palma and Pinhal Grande-RS. The units represent the integration of geo-environmental characteristics of the physical elements of the study area, compared to social activities, developed by occupation who developed and transformed the local landscape. The methodology uses a systems approach to landscape using tools like GIS (Geographic Information Systems). Through a representation of synthesis, were defined four systems and 5 units, which characterized the landscape of the cities in geoenvironmental studies. The system is composed of the Urban thirst of the five municipalities in the study. The system Slopes of Border Plateau is divided into two main units: Colinas in Sedimentary Rocks of Hill, with human occupation and signifitiva; Relief Unit of the Border Plateau escarpment, where there are higher concentrations of woody vegetation and susceptibility of occurrence of processes mass movement. System in Rice Paddies ramps Recent Deposits anthropic action results in environmental conflicts primarily as the occupation in areas of permanent preservation areas. Furthermore, there is susceptibility becomes risky areas in flood periods. The system Colinas Plateau was divided into three main units with differentiation as to occupation and geomorphological processes, which are: Volcanic Hills with Medium Properties, Small Properties with Hills Volcanic Hills and Rocks Altitudes in friable. In this sense this work can provide a theoretical and methodological framework, advanced to study and verification of the potential environmental and restrictions, allowing proposals for sustainable development communities, as well as serve as a basis for conducting further studies in these municipalities.